2015
DOI: 10.1021/acs.jproteome.5b00804
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free LC–MS/MS Proteomic Analysis of Cerebrospinal Fluid Identifies Protein/Pathway Alterations and Candidate Biomarkers for Amyotrophic Lateral Sclerosis

Abstract: Analysis of the cerebrospinal fluid (CSF) proteome has proven valuable to the study of neurodegenerative disorders. To identify new protein/pathway alterations and candidate biomarkers for amyotrophic lateral sclerosis (ALS), we performed comparative proteomic profiling of CSF from sporadic ALS (sALS), healthy control (HC), and other neurological disease (OND) subjects using label-free liquid chromatography-tandem mass spectrometry (LC-MS/MS). A total of 1,712 CSF proteins were detected and relatively quantifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 112 publications
4
61
0
6
Order By: Relevance
“…Recent proteomic analyses identified 248 proteins in the CSF from both healthy controls and patients with ALS that exhibited enrichment in biologic roles related to the complement cascade and acute inflammation [47]. Additionally, studies in our group using unbiased proteomic analyses of CSF also identified that acute inflammatory responses and complement activation were among the top pathways altered in the CSF of patients with ALS when compared with healthy controls and other neurologic diseases [10]. Therefore, inflammatory mediators present potential biomarkers for ALS.…”
Section: Biomarkers Of Inflammationmentioning
confidence: 84%
See 1 more Smart Citation
“…Recent proteomic analyses identified 248 proteins in the CSF from both healthy controls and patients with ALS that exhibited enrichment in biologic roles related to the complement cascade and acute inflammation [47]. Additionally, studies in our group using unbiased proteomic analyses of CSF also identified that acute inflammatory responses and complement activation were among the top pathways altered in the CSF of patients with ALS when compared with healthy controls and other neurologic diseases [10]. Therefore, inflammatory mediators present potential biomarkers for ALS.…”
Section: Biomarkers Of Inflammationmentioning
confidence: 84%
“…ALS is a complex disease associated with numerous pathologic mechanisms, including oxidative stress, mitochondrial dysfunction, axonal damage, microglial activation, inflammation, excitotoxicity, and protein aggregation [7][8][9][10][11]. Current diagnostic measures rely upon clinical examination and electrophysiological measurements [6,12], which, in most cases, have not enabled early diagnosis where potential therapies would likely be most effective.…”
Section: Introductionmentioning
confidence: 99%
“…Both animal models and postmortem tissue from ALS patients shows infiltration of activated microglia and T cells into affected areas, which correlates with progression rate. 10,11 We applied a state-of-the-art high-throughput MS method to enable in-depth characterization of individual longitudinal CSF samples from a large, clinically well-characterized ALS cohort, in comparison to healthy and disease control groups. 6,7 Differential expression of cytokines, including factors specifically involved in microglial activation, have been observed in enzyme-linked immunosorbent assay (ELISA)-based studies of CSF from ALS patients.…”
mentioning
confidence: 99%
“…Blocking accumulation of misfolded SOD‐1 in mitochondria by elevating the cytokine macrophage migration inhibitory factor (MIF) enhances neuronal survival (36). In addition, proteomic analysis of cerebrospinal fluid (CSF) samples of patients with sALS, in comparison to control CSF samples, revealed enrichment of proteins related to inflammation (in particular complement components) and decreased levels of proteins related to synaptogenesis and extracellular matrix organization (37).…”
mentioning
confidence: 99%